Pengaruh Growth Mindset terhadap Ketekunan Akademik dan Resiliensi pada Siswa yang Mengalami Kegagalan - Wahdania Wahdania; Nadia Nadia; Risma Anita Putiani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The influence of a growth mindset on the motivation, persistence, and resilience of students experiencing failure is a major concern in today's education world, given the importance of overcoming academic obstacles and building psychological resilience. This research is motivated by the high rates of learning failure and academic stress experienced by students, and the need for strategies that can improve their resilience and mental well-being. The purpose of this study is to comprehensively analyze the influence of a growth mindset on student academic persistence and resilience through a literature review and case studies. The method used was a literature review, reviewing 18 scientific journals from 2023 to 2025, including a qualitative analysis of various growth mindset implementation strategies and their impact on students. The primary data obtained indicate that a growth mindset plays a significant role in increasing learning motivation, the ability to manage failure, and resilience to academic stress, as well as strengthening students' psychological well-being. These key findings confirm that consistent implementation of a growth mindset through training, curriculum, and guidance and counseling services can help students recover from failure and improve academic achievement sustainably. The study concludes that a growth mindset is a crucial factor in developing student potential and needs to be integrated into educational policies and guidance and counseling services to create more resilient and empowered students.